1986
DOI: 10.1111/j.1600-0714.1986.tb00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence in the assessment of polymorphonuclear leukocyte function in chronic inflammatory periodontal disease

Abstract: Polymorphonuclear neutrophils (PMN's) constitute the primary host resistance factor against infection. They are prominent cells in both the gingival tissue and gingival sulcus in most forms of periodontal disease. Although defective PMN function has been implicated in the pathogenesis of localized juvenile periodontitis (UP) and rapidly progressive periodontitis (RPP), this may not necessarily be the case in adult periodontitis (AP). A number of studies have failed to detect PMN dysfunction in AP. However, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The exposure of bacteria to low H202 concentrations results in the induction of 30 proteins and resistance to killing by higher doses of H202 (Storz and Tartaglia, 1992 (Seymour et al, 1986). PMN possess at least 2 main pathways for controlling micro-organisms (i.e., oxidative and non-oxidative) which either kill bacteria, influence bacterial growth, or modify bacterial colonization in relation to the periodontium (Miyasaki, 1991 (Seymour et al, 1986;McCord, 1993 (Seymour et al, 1986). The ROS produced by PMN during phagocytosis oxidize the cyclic hydrazine 5-amino-2,3dihy-dro-1,4phthalazinedione (luminol) to an excited 3-aminophthalate anion that relaxes to the ground state with emission of light (Battino et al,199 la absorbance at 550 nm due to cytochrome c reduction.…”
Section: Regulation Of "Anti-oxidant Genes"mentioning
confidence: 99%
“…The exposure of bacteria to low H202 concentrations results in the induction of 30 proteins and resistance to killing by higher doses of H202 (Storz and Tartaglia, 1992 (Seymour et al, 1986). PMN possess at least 2 main pathways for controlling micro-organisms (i.e., oxidative and non-oxidative) which either kill bacteria, influence bacterial growth, or modify bacterial colonization in relation to the periodontium (Miyasaki, 1991 (Seymour et al, 1986;McCord, 1993 (Seymour et al, 1986). The ROS produced by PMN during phagocytosis oxidize the cyclic hydrazine 5-amino-2,3dihy-dro-1,4phthalazinedione (luminol) to an excited 3-aminophthalate anion that relaxes to the ground state with emission of light (Battino et al,199 la absorbance at 550 nm due to cytochrome c reduction.…”
Section: Regulation Of "Anti-oxidant Genes"mentioning
confidence: 99%
“…Under pathological conditions, a disturbance in favour of ROS production results in oxidative stress (Curnutte & Babior 1987, Sies 1991, Chapple 1996, Halliwell 1996. Excess production of ROS has been implicated in the pathogenesis of many human diseases and, more recently, periodontitis (Seymour et al 1986, Curnutte & Babior 1987, Whyte et al 1989, Sies 1991, Kimura et al 1993, Shapira et al 1994, Halliwell 1996, Chapple 1997, Asman 1998.…”
mentioning
confidence: 99%
“…These studies have shown that the elastase activity per //I was higher in sites with attachment loss (Gustafsson et al, 1992) and that the increase in elastase activity was associated with a decrease in the concentration of the protease inhibitor a-2-macroglobulin. indicating an increased protease activity (Gustafsson et al, 1994a), We also found that the ratio between elastase and lacloferrin was higher in GCF from sites without attachment loss in patients with periodontitis than iti GCF from clinically similar sites in patients with gingivitis alone (Gustafsson et al, 1994b), Moreover, when comparing these two kinds of sites we also found lower total protein concentrations in GCF from sites in patients with periodontitis (Gustafsson et al, 1995), Together, these findings suggest an increased release of elastase from the neutrophils in patients with periodontitis and indicate a patient-specific neulrophii-associated host response, characterised by a tissue destructive inflammatory reaction, has shown increased degranulation of elastase from in vitro-actnated neutrophils in patients with juvenile periodontitis afler Fc;-receptor {Fc;-R) slimulation, A well-established way to quantify neutrophil activity is to measure the release of free oxygen radicals with luminol-enhanced chetniluminescence (CL) (Ewetz et al, 1981. Seymour et al, 1986, A number of studies have shown increased CL from neutrophils in young patients with periodontitis (Asman et al, !984.…”
mentioning
confidence: 99%